Infrastruktura osadnicza w gospodarce regionalnej – kwestie równoważenia rozwoju - Cesarski, Maciej (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
In this study I try to prove that the effects of economic development concentrate in the area of settlement which is underpinned by settlement infrastructure. Balancing the development of this infrastructure constitutes therefore the base for balancing the regional economy. Issues of sustainable development of settlement infrastructure can be divided into two aspects. The first is the effect of balancing the development of infrastructure for harmonious development of civilization subordinated to the principles of sustainable development. The second is to prevent increase in infrastructure disparities. The primary objective of this paper is analytical summary of saturation in flats and the number of seats in theaters, cinemas etc. by voivodships in Poland in the period 2006–2010. The results of the analysis indicate that the saturation in fl ats in Poland is increasing in all voivodships but in varying degrees. The number of seats in theaters, cinemas, etc. decreases or increases depending of region.